Perancangan User Interface pada Aplikasi Rekomendasi Tempat Wisata di Daerah Gianyar - Mahagangga, Made Dhandy Satria; Astuti, Luh Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
Bali, a beautiful island in Indonesia, offers the perfect combination of natural beauty, rich culture, and the friendliness of its people. Known for its stunning beaches, clear sea water, and stunning rice terraces, Bali is a popular tourist destination worldwide. In addition, the rich cultural life with religious ceremonies, traditional dances and sculpture makes Bali a center for artistic and cultural activities. Tourists can enjoy an unforgettable experience while exploring ancient temples, visiting traditional markets or interacting with the friendly locals. Bali is a mesmerizing paradise that promises a life full of adventure and peace. The purpose of this research is to build a recommendation system for tourist attractions which is expected to be able to make it easier for tourists who are on vacation to Bali to find tourist attractions they want to go to, especially in the Gianyar area. Keywords : Applications, Android, UML, Recommendation, Tourist Attraction